Pendidikan Karakter Berbasis Ta’dîb - Adian Husaini (TSAQAFAH, 2013)
At the moment, Indonesian government campaigns for education based on character rapidly. Various theories have been proposed to make this mission success. Unfortunately, the government tends to use the secular’s theories which so far from religious values, whereas Indonesia is the biggest nation with Muslims population in the world. Righteously, the education which based on character should be taken from this Religion’s precepts. Actually, this idea has been engaged by the founding father of this country. In the principle’s foundation of this country (Pancasila), the founding father formulate some principle which using Islamic terms. As an example, in second principle, we can find word ‘Adil’ and ‘Adab’ which both of these words is Islamic term that considered as Islamic basic vocabulary and closely related with Islam’s precepts. Because of this importance, the founding father used this words and Islamic terms inside the principle’s foundation of this country (Pancasila). These indicates how strong the influences of Islamic worldview in prefatory’s constitution of this country (Pembukaan UUD 1945). Therefore, we have to understanding these Islamic terms (adab and adil) with Islamic worldview. Because of the importance of this ‘Adab’ term, then this is the time when the government use these term in implementation of education based on character in this country.